Strategy Promotion Through Instagram National Aid Foundation (BAZIS) DKI Jakarta in Increasing Zakat Fundraising - Ahmad, Habibullah; Zen, Muhamad; Shabri, Nabilla Aulia (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2025)
This study aims to explores the initiatives undertaken by BAZNAS (BAZIS) Jakarta to boost charity fundraising through Instagram, particularly in light of the prevalent lack of public awareness regarding zakat. Social media platforms, especially Instagram, have become crucial due to their extensive reach and high levels of audience engagement. The research employs a qualitative methodology, utilizing interviews, observations, and documentation conducted at BAZNAS (BAZIS) Jakarta. The findings reveal that BAZNAS (BAZIS) Jakarta effectively enhanced its charity fundraising efforts by leveraging a promotional mix that includes advertising, personal selling, sales promotion, public relations, and direct marketing. Additionally, the application of the AIDA technique attracting attention, generating interest, creating desire, and prompting action played a significant role in this success. This achievement was further reinforced by the strategic use of Instagram features to broaden outreach and elevate audience engagement.